2016
DOI: 10.1016/j.rbre.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Myelopathy in systemic lupus erythematosus: clinical, laboratory, radiological and progression findings in a cohort of 1,193 patients

Abstract: Myelopathy occurred in 14 (1.2%) of the patients in our cohort and this may be the first manifestation of the disease occurring independently of systemic disease activity. Although rare, myelopathy shows great morbidity and mortality, can be recurrent and MRI is critical for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
3
11
1
2
Order By: Relevance
“…We found that the majority of patients developed TM after the diagnosis of SLE, a nding which is consistent with those of previous studies [4,[15][16][17][18]. Of note, the diagnosis of SLE-associated TM is usually simple when the TM occurs in the background of SLE, while the development of TM as the rst manifestation of SLE may pose a challenge to SLE diagnosis due to the heterogeneity of presenting clinical characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the majority of patients developed TM after the diagnosis of SLE, a nding which is consistent with those of previous studies [4,[15][16][17][18]. Of note, the diagnosis of SLE-associated TM is usually simple when the TM occurs in the background of SLE, while the development of TM as the rst manifestation of SLE may pose a challenge to SLE diagnosis due to the heterogeneity of presenting clinical characteristics.…”
Section: Discussionsupporting
confidence: 90%
“…Transverse myelitis in association with APS is rare, with an estimated prevalence of approximately 1% [ 12 , 19 ] presenting with symmetrical paraparesis, sensory loss and sphincter dysfunction. As with many of the neurological manifestations associated with APS, transverse myelitis is also seen in patients with SLE and that is where most of the literature is focused [ 120 , 121 ].…”
Section: Manifestations Other Than Cerebrovascular Diseasementioning
confidence: 99%
“…When considering inflammatory or infections etiologies of myelopathy, visualization of the osseous spinal column as well as the spinal cord is useful and best accomplished noninvasively by MRI [4,7,45,[52][53][54][55][56][57][58][59][60].…”
Section: Discussion Of Procedures By Variant Variant 1: Acute Onset Myelopathy Initial Imagingmentioning
confidence: 99%